Multibeam bathymetry raw data (SeaBeam 1050 entire dataset) of RV POSEIDON during cruise POS385 - Wintersteller, Paul; Klaucke, Ingo; Hebbeln, Dierk (PANGAEA, 2025)
Raw bathymetry data were collected using SeaBeam 1050 multibeam echosounder during the RV POSEIDON cruise POS385 "Cold-Water Corals of the Alboran Sea (western Mediterranean Sea)". The cruise took place between 2009-05-29 and 2009-06-16 (Faro, Portugal - Toulon, France). The focus of the cruise was to investigate cold-water coral ecosystems in the Strait of Gibraltar and in the Alboran Sea. Bathymetry data were collected in search for locations for ROV surveys and sediment sampling. Calibration data of the MBES collected on 2009-05-30 are included into this dataset. Five target areas were mapped at 1) Malaga Mounds, 2) EI Idrissi Bank, 3) East Melilla Area, 4) Adra Ridge & Alboran Ridge, 5) Chella Bank. Sound velocity profiles (SVP) were acquired at 3 CTD stations (Malaga Mounds, EI Idrissi Bank, and East Melilla Area), and are part of this dataset. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. Data are unprocessed and therefore contain incorrect depth measurements (artifacts). Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).
Keywords: Bathymetry; Multibeam Echosounder